Handbook of Halal Food Production - Riaz, Mian N.; Chaudry, Muhammad M.; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
Until now, books addressing Halal issues have focused on helping Muslim consumers decide what to eat and what to avoid among products currently on the market. There was no resource that the food industry could refer to that provided the guidelines necessary to meet the Halal requirements of Muslim consumers in the United States and abroad.Handbook of Halal Food Production answers this need by summarizing the fundamentals of Halal food production, serving as a valuable reference for food scientists, food manufacturers, and other food industry professionals. This text delivers a wealth of information about Halal food guidelines for food production, domestic and international food markets, and Halal certification. Among chapters that cover production requirements for specific foods such as meat and poultry, fish and seafood, and dairy products, there are other chapters that address global Halal economy, Muslim demography and global Halal trade, and comparisons among Kosher, Halal and vegetarian. In addition, the book presents Halal food laws and regulations, HACCP and Halal and general guidelines for Halal food Production. For persons targeting the Halal food market for the first time, this book is particularly valuable, providing understanding of how to properly select, process, and deliver foods. In light of the increasing worldwide demand for Halal food service, branded packaged food, and direct-marketed items, this volume is more than an expert academic resource; it is a beneficial tool for developing new and promising revenue streams. Both editors are food scientists who have practical experience in Halal food requirements and Halal certification and the contributors are experts in the Halal food industries.
Chapter 1 Introduction -- --Mian N. Riaz and Munir M. Chaudry -- Chapter 2 --Halal Food Laws and Regulations -- --Mian N. Riaz and Munir M. Chaudry -- Chapter 3 --General Guidelines for Halal Food Production -- --Mian N. Riaz and Munir M. Chaudry -- Chapter 4 --Muslim Demography and Global Halal Trade: A Statistical Overview -- --Mohammed A. Khan, Mian N. Riaz, and Munir M. Chaudry -- Chapter 5 --Global Halal Economy -- --Rafiuddin Shikoh, Mian N. Riaz, and Munir M. Chaudry -- Chapter 6 --Animal WelfareKristin Pufpaff, Mian N. Riaz, and Munir M. Chaudry -- Chapter 7 --The Religious Slaughter of Animals: A US Perspective on -- Regulations and Animal Welfare Guidelines -- --Joe Regenstine, Mian N. Riaz, and Munir M. Chaudry -- Chapter 8 --Halal Production Requirements for Meat and Poultry -- --Kristin Pufpaff, Mian N. Riaz, and Munir M. Chaudry -- Chapter 9 --Halal Processed Meat Requirements -- --Mustafa Farouk, Mian N. Riaz, and Munir M. Chaudry -- Chapter 10 --Halal Production Requirements: For Fish and Seafood -- --Mian N. Riaz, Rafiuddin Shaik, and Munir M. Chaudry -- Chapter 11 --Halal Production Requirements for Dairy Products -- --Mian N. Riaz and Munir M. Chaudry -- Chapter 12 --Halal Production Requirements for -- Cereals and Confectionaries -- --Mian N. Riaz and Munir M. Chaudry -- Chapter 13 --Enzymes in Halal Food Production -- --Mian N. Riaz and Munir M. Chaudry -- Chapter 14 --Gelatin in Halal Food Production -- --Mian N. Riaz and Munir M. Chaudry -- Chapter 15 --Flavors, Flavorings, and Essences in Halal Food -- --Eric Butrym, Laura LaCourse, Mian N. Riaz, and -- Munir M. Chaudry -- Chapter 16 --Alcohol in Halal Food Production -- --Roger Ottman, Mian N. Riaz, and Munir M. Chaudry -- Chapter 17 --Food Additives and Processing Aids -- --Mian N. Riaz and Munir M. Chaudry -- Chapter 18 --Food Ingredients in Halal Food Production -- --Mian N. Riaz and Munir M. Chaudry -- Chapter 19 --Halal Production Requirements for Nutritional Food Supplements -- --Mian N. Riaz and Munir M. Chaudry -- Chapter 20 --Biotechnology and GMO Ingredients in Halal Foods -- --Mian N. Riaz and Munir M. Chaudry -- Chapter 21 --Animal Feed and Halal Food -- --Mian N. Riaz and Munir M. Chaudry -- Chapter 22 --Halal CosmeticsMian N. Riaz and Munir M. Chaudry -- Chapter 23 --Labeling, Packaging, and Coatings for Halal Foods -- Mian N. Riaz and Munir M. Chaudry -- Chapter 24 --How to Get Halal Certified -- --Mian N. Riaz and Munir M. Chaudry -- Chapter 25 --Comparison of Kosher, Halal, and Vegetarianism -- --Mian N. Riaz and Munir M. Chaudry -- Chapter 26 --Globalization of Halal Certification: From an Industrial -- Perspective -- --Jes Knudsen, Mian N. Riaz, and Munir M. Chaudry -- Chapter 27 --Testing Non-Halal Materials -- --Winai Dahlan, Mian N. Riaz, and Munir M. Chaudry -- Chapter 28 --Potential Hazards and Sanitation of Halal Facilities -- --Mian N. Riaz and Munir M. Chaudry -- Chapter 29 --Halal Awareness and Education Schemes -- --Mian N. Riaz and Munir M. Chaudry -- Chapter 30 --Halal Food Model -- --Mian N. Riaz and Munir M. Chaudry -- Chapter 31 --Haccp and Halal -- --Mian N. Riaz, Sibte Abbas, and Munir M. Chaudry -- Appendix A: Key Terminology from Other Languages -- Appendix B: Permitted Food Additives in the European Union -- Appendix C: Ingredient List -- Appendix D: Codex Alimentarius
Includes bibliographical references and index.
Also available in print format.
Keywords: Food industry and trade -- Standards; Halal food; Halal food industry; TECHNOLOGY & ENGINEERING / Food Science; Electronic books